KETAMINE IN PREHOSPITAL MANAGEMENT OF TRAUMATIC BRAIN INJURIES: FROM CONTROVERSY TO ROUTINE USE. A SYSTEMATIC REVIEW OF CURRENT LITERATURE - Radosław Krzysztof Binkowski; Rafał Bednarczyk; Natalia Bednarczyk; Agnieszka Kurek; Natalia Krajewska; Aleksandra Lejman; Aleksandra Mazurkiewicz; Hubert Sidor; Monika Wołosik; Szymon Zysiak (International Journal of Innovative Technologies in Social Science, 2026)
Research Objectives: To present the broadest available evidence regarding the safety and efficacy of ketamine in traumatic brain injury (TBI) and explain the evolution of clinical guidelines. This review aims to verify historical contraindications against current knowledge and demonstrate how ketamine's role has evolved from a contraindicated drug to a potentially beneficial therapeutic option in prehospital settings.Methods: Systematic analysis of clinical studies and systematic reviews examining ketamine's effects on cerebral hemodynamics, intracranial pressure (ICP), and cerebral perfusion pressure (CPP). Evaluation of ketamine's utility as an analgesic-sedative drug in prehospital TBI care, including assessment of safety profiles and clinical outcomes across civilian and military settings.Conclusions: Ketamine's effect on cerebral hemodynamics is at least neutral and often beneficial, contrary to historical concerns about increased ICP. The drug demonstrates high utility as a prehospital analgesic-sedative agent, providing effective pain control and sedation without compromising patient safety. Historical contraindications must be regularly re-verified in light of current evidence. Clinical guidelines have evolved significantly, reflecting growing recognition that proper ventilation control and hemodynamic monitoring eliminate previous safety concerns. Current evidence supports ketamine as a safe and potentially advantageous therapeutic option in prehospital TBI management, particularly for achieving rapid sequence intubation, maintaining hemodynamic stability, and preventing secondary brain injury in emergency settings.